Actuación sindical en la prevención y combate al acoso moral en el ambiente de trabajo: ¿es efectiva? - Ciampa Benhame Puglisi, Maria Lúcia (Pontificia Universidad Católica del Perú, 2019)
In recent years, workplace harassment cases have multiplied and ceased to be reserved from one or another society to become a common reality of our times. Although there has been an attempt to solve this problem from legislative policies, it is also important to consider the role of trade unions. In this article, the author examines from web platforms the eff ect and presence of trade unions on specifications in the prevention and fi ght against psychological harassment on Brazil workplaces. To achieve this, comparative case law, union agreements and news from Brazil and other countries press agencies have been considered.

Las situaciones de acoso laboral se han multiplicado y han dejado de ser propias de una u otra sociedad para hacerse una realidad común a nuestros tiempos. Se ha intentado dar solución a esta problemática desde el diseño de políticas legislativas, pero también es importante considerar y cuestionar el papel de los sindicatos. En este artículo, la autora evalúa, desde una muestra de plataformas web, el impacto y la presencia de los sindicatos en acciones efectivas para prevenir y reducir el acoso moral en los centros de trabajos de Brasil. Para ello, considera el análisis de jurisprudencia comparada, acuerdos sindicales y noticias tanto de centros de la región como de otros sistemas ante estos casos son considerados.
Trade union action in the prevention and fight against psychological harassment at the workplace: is it effective?
Keywords: Acoso moral; Prevención y combate; Sindicato; Acción sindical; https://purl.org/pe-repo/ocde/ford#5.05.01